Bug bounty hunting for web security : find and exploit vulnerabilities in web sites and applications - Sinha, Sanjib (Apress, 2019)
Taking a close look at the types of tools available to you, this book explains how learning to find vulnerabilities in websites will help you become a better penetration tester. --